Emptiness Through the Perspective of Existentialism and Religion in the Digital Age - Nandini, Shafira Yasmin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
This study aims to provide an understanding of how the emptiness is felt by humans, especially in the digital era through the philosophical views of existentialism and religion. The research conducted is qualitative in nature and uses library research methods sourced from books, journals, dictionaries, and other scientific articles. The emptiness felt by humans as research objects is analyzed descriptively to create a comprehensive understanding. The results of this study found that the emptiness felt by humans in the digital era can occur due to digital dependency and fatigue, which is closely related to the perspective of human existence at the aesthetic and ethical stages. In addition, emptiness can also appear suddenly which can be related to existential problems or psychological mechanisms. To overcome the emptiness so far discovered is to move on to a higher stage of human existence, ending with a religious stage which also represents a view of emptiness through a religious perspective. However, religious views still suggest that digital technology in human life is something negative, while if it is used wisely, digital technology should be able to carry out its function as a means of fulfilling the needs of human life instead of becoming a potential source of emptiness.